2021
DOI: 10.3389/fpubh.2021.658876
|View full text |Cite
|
Sign up to set email alerts
|

What Do Adolescents Know About One-Health and Zoonotic Risks? A School-Based Survey in Italy, Austria, Germany, Slovenia, Mauritius, and Japan

Abstract: More than 60% of the 1,700 infectious diseases that affect human come from animals and zoonotic pandemics, after starting from sporadic phenomena limited to rural areas, have become a global emergency. The repeated and frequent zoonotic outbreaks such as the most recent COVID-19 pandemic can be attributed also to human activities. In particular, the creation of enormous intensive domestic animal farms, the indiscriminate use of antibiotics, the destruction of forests, the consumption of the meat of wild animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In addition, we found that some practices such as having mouth contact with the animals, touching pet feces, and do not always wash their hands after contact with their pets are similar to results found in Ethiopia [39], where 14.9% of high school students haring the same house with animals; 24.2% feed their pets with raw food, and 16.7% did not vaccinate their pets; and in Italy, Austria, Germany, Slovenia, Mauritius, and Japan almost 24% of the students are unaware that pets must be dewormed [28], those results exposes them to a tangible risk of being infected by zoonotic parasitic diseases such as Giardia or Toxocara.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, we found that some practices such as having mouth contact with the animals, touching pet feces, and do not always wash their hands after contact with their pets are similar to results found in Ethiopia [39], where 14.9% of high school students haring the same house with animals; 24.2% feed their pets with raw food, and 16.7% did not vaccinate their pets; and in Italy, Austria, Germany, Slovenia, Mauritius, and Japan almost 24% of the students are unaware that pets must be dewormed [28], those results exposes them to a tangible risk of being infected by zoonotic parasitic diseases such as Giardia or Toxocara.…”
Section: Discussionsupporting
confidence: 79%
“…In Ethiopia, the information shows that 76.8% of high school students had heard about zoonoses [24]. In Malaysia, the 11% [25], in a previous study in Nariño, Colombia, and Usme, the authors found that 63% and 74.6% of the respondent had heard about the term zoonoses [26,27], in Austria, Germany, Slovenia, Mauritius, and Japan 67.84% of adolescents know the meaning of the term zoonoses [28]. However, in Brazil, only 28.2% had heard the term zoonosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Through the direct-to-consumer policy, puppies are shipped from the producers/international distributors to buyers without relying on traditional stores or other middlemen [ 54 ]. Although the main targets of illegal pet trafficking are families and adolescents, a high proportion of adolescents does not know that most infectious diseases affecting humans come from an animal reservoir [ 6 ]. Therefore, the main target of illegal trafficking is even more exposed to zoonotic risk as largely ignorant.…”
Section: Discussionmentioning
confidence: 99%
“…The final aim of the project was to tackle the illegal animal trade through a cross-border cooperation approach, to monitor the health status of traded animals and to protect the health and safety of EU citizens [ 1 ]. Indeed, from a sanitary perspective, the illegal animal trade can facilitate the spread across borders of pathogens relevant to both animal and public health [ 3 , 4 , 5 , 6 ]. The strategy included the synergic cooperation among veterinary public health, justice and law enforcement through the involvement of the international police and custom cooperation centers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research, with a similar approach to ours, investigated adolescents’ knowledge concerning One Health [ 41 ], which should likewise be regarded as a high-priority theme in educational interventions [ 42 ]. Nonetheless, to the best of our knowledge, this research is the first study worldwide that investigates the effectiveness of a school-based intervention on Urban Health knowledge in a student population, and it can be considered a pilot study for future research.…”
Section: Discussionmentioning
confidence: 99%